The Impact of Carbohydrate Solutes on the Ionicity of 1-Ethyl-3-Methylimidazolium Acetate Ionic Liquid Solutions. (23rd July 2018) - Fahey, Patrick J.; Durkin, David P.; Fox, Eric T.; Gobet, Mallory; Greenbaum, Steven; De Long, Hugh C.; Trulove, Paul C.
Abstract : Changes in ionicity were evaluated for dissolved cellulose, cellobiose, and glucose in 1-ethyl-3-methylimidazolium acetate (EMIAc) and 1:1-mole-ratio mixtures of EMIAc with acetonitrile (1:1 EMIAc:AN) and water (1:1 EMIAc:H2 O). Test solutions were made with these three solvent types by dissolving 0.1, 0.5, 1.0, and 3.0 wt.-% of either cotton, microcrystalline cellulose (MCC), cellobiose, or glucose. EMIAc's ionicity decreased with the 1:1 addition of AN by 27 and 19 % at 20 and 60°C, respectively, and EMIAc's ionicity increased with the 1:1 addition of H2 O by 13 and 22 % at 20 and 60°C, respectively. No significant changes in ionicity were observed with the addition of the carbohydrate solutes. Solutes' negligible changes to ionicity are consistent with how these low-concentrations of solutes produce similar decreases in molar conductivity at given solute content for a given solvent type, suggesting the ion aggregation and conductivity behavior remain unchanged with solute up to 3.0 wt.-%.